The Emerging Role of D-2-Hydroxyglutarate as an Oncometabolite in Hematolymphoid and Central Nervous System Neoplasms - Rakheja, Dinesh; Medeiros, L J.; Bevan, Scott; Chen, Weina (Frontiers in Oncology, 2013)
Approximately 20% of unselected cases and 30% cytogenetically diploid cases of acute myeloid leukemia (AML) and 80% of grade II–III gliomas and secondary glioblastomas carry mutations in the isocitrate dehydrogenase (IDH) 1 and 2 genes. IDH1/2 mutations prevent oxidative decarboxylation of isocitrate to α-ketoglutarate (α-KG) and modulate the function of IDH (neomorphic activity) thereby facilitating reduction of α-KG to D-2-hydroxyglutarate (D-2HG), a putative oncometabolite. D-2HG is thought to act as a competitive inhibitor of α-KG-dependent dioxygenases that include prolyl hydroxylases and chromatin-modifying enzymes. The end result is a global increase of cellular DNA hypermethylation and alterations of the cellular epigenetic state, which has been proposed to play a role in the development of a variety of tumors. In this review, we provide an update on potential molecular mechanisms linking IDH1/2 mutations and the resulting oncometabolite, D-2HG, with malignant transformation. In addition, in patients with AML and glioma we focus on the associations between IDH1/2 mutations and clinical, morphologic, cytogenetic, and molecular characteristics.